2019
DOI: 10.21815/jde.019.100
|View full text |Cite
|
Sign up to set email alerts
|

Lean Methods Applied to CAD/CAM Pedagogy in the Dental Simulation Laboratory

Abstract: Dental education is incorporating computer‐assisted design/computer‐assisted manufacturing (CAD/CAM) into patient care delivery. The aim of this study was to determine if lean production methods applied to the preclinical phase of dental education would reduce the students’ time (efficiency) to complete CAD/CAM indirect restorations (CAD/CAM IR) without compromising the desired quality of the CAD/CAM tooth preparations (effectiveness). In 2016, all third‐year students at one U.S. dental school were randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…These characteristics are recognised by faculty and students who showed favourable views of CAD/CAM as an complementary assessment tool for tooth preparations. 22,26,27 This comes in line with our survey study that demonstrated the students' agreement on the usefulness of the digital technology as a valuable method to see the damage to nearby teeth, smoothness of walls, depth of preparation, convergence/divergence walls, isthmus, bevel and outline shape.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These characteristics are recognised by faculty and students who showed favourable views of CAD/CAM as an complementary assessment tool for tooth preparations. 22,26,27 This comes in line with our survey study that demonstrated the students' agreement on the usefulness of the digital technology as a valuable method to see the damage to nearby teeth, smoothness of walls, depth of preparation, convergence/divergence walls, isthmus, bevel and outline shape.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, digital assessment may also augment the educator's perceptions with tools that allow visualisation and measurement of dental performance in different planes and directions. These characteristics are recognised by faculty and students who showed favourable views of CAD/CAM as an complementary assessment tool for tooth preparations 22,26,27 …”
Section: Discussionmentioning
confidence: 99%
“…The lack of knowledge and skills is one of the most important factors limiting technology's efficient integration and utilization in dentistry (Matthews et al 2016). Therefore, many dental schools in the US have started to incorporate the most recent digital technologies in their curricula to provide students with the knowledge and skills necessary to keep pace with the rapidly growing need for the implementation of digital techniques and workflows in dentistry (Gratton et al 2016;Schlenz et al 2020;Kutkut and Okeson 2022;Siegel et al 2019;Afshari et al 2017;Ishida et al 2022;Prager et al 2020Prager et al , 2022AlKindi et al 2018;Jurado et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to Murphy et al, 14 "Dental students tend to prefer visualization learning more than students from other majors." As mentioned by Siegel et al, 15 dental students are prepared for developing technologies and treatments, and the educational curricula should reflect this trend. Only 13.5% of the students owned computers with specifications that met the operating system, CPU, core, and RAM conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ preferences are also high. According to Murphy et al., 14 “Dental students tend to prefer visualization learning more than students from other majors.” As mentioned by Siegel et al., 15 dental students are prepared for developing technologies and treatments, and the educational curricula should reflect this trend.…”
Section: Discussionmentioning
confidence: 99%